HUBUNGAN ANTARA ADIKSI INTERNET DENGAN PROKRASTINASI AKADEMIK PADA SISWA SMKN X INDRAMAYU - Mikaella Audrey Setiawan Putri; Denrich Suryadi (Provitae: Jurnal Psikologi Pendidikan, 2023)
Internet use by adolescents has increased in recent years, which brings negative effects for adolescents, namely internet addiction. Internet addiction can affect the level of academic procrastination in adolescent students. In some previous studies it was found that there was a relationship between the two variables, but it was not yet known in adolescents living in rural areas. The purpose of this study was to determine the relationship between internet addiction and academic procrastination in adolescents living in one of the villages in Indramayu. Internet addiction was measured using the Internet Addiction Test and academic procrastination was measured using the Procrastination Assessment Scale for Students. The criteria for participants in this study were adolescents who lived in rural areas and actively used devices to use the internet. The research participants totaled 253 people using purposive sampling technique. Based on the results of data processing, it can be concluded that there is a significant relationship between internet addiction and academic procrastination in adolescents living in rural areas (p < .05, r = .277).